Soil Test Crop Response Correlation Approach for Summer Groundnut in Inceptisol - Archana Pawar, A.N. Deshpande, V.K. Shiralkar (Journal of the Indian Society of Soil Science, 2016)
Field experiment to develop fertilizer prescription equation for summer groundnut was conducted at Central Farm of PGI, MPKV, Rahuri during 2010-11 on the basis of soil test crop response approach. Soil test data, yield and NPK uptake by groundnut were used for obtaining four important basic parameters viz., nutrient required to produce one quintal of groundnut grain, contribution of nutrients from fertilizers, contribution of nutrients from soil and contribution of nutrients from FYM (%CFYM). It was found that 3.98, 0.95 and 0.91 kg N, P2O5 and K2O, respectively, were required for producing 1 q summer groundnut. The per cent contribution of nutrients from soil, fertilizer and FYM were 49.66, 66.65 and 3.47 for N; 53.41, 24.63 and 26.22 for P2O5 and 2.95, 60.74 and 10.33 for K2O, respectively. Yield targeting equations were developed by using these basic parameters, and based on these equations, ready reckoner of NPK fertilizer doses with and without FYM application was prepared for varying soil test values and desired yield targets of summer groundnut.